101 mathematical projects : a resource book - Bolt, Brian, ....-; Hobbs, David, ....- (Cambridge : Cambridge University Press, 2005)
This book for teachers suggests projects which cater for a wide range of concepts and skills, and links with other curriculum subjects.
Keywords: Wiskunde -- Didactiek